The impact of information on the stock market . - Айтмаганбетова, Н. (Journal of Economic Research & Business Administration, 2015)
The paper examines the impact of information on the stock exchange . In addition , the analysis of the situation on the stock market of the Republic of Kazakhstan .Some problems related to access to information,and provides solutions.